Public health and budget impacts of switching from a trivalent to a quadrivalent inactivated influenza vaccine in Paraguay - Antonio Arbo; Celia Martinez-Cuellar; Cynthia Vazquez; Lucile Bellier; Cecilia Adorno; Hugo Dibarboure; Juan Guillermo Lopez; Audrey Petitjean; Pablo Bianculli (Taylor & Francis Group, 2022)
This study aimed to investigate the public health and economic benefit of using a quadrivalent influenza vaccine (QIV) instead of a trivalent influenza vaccine (TIV) in past seasons in Paraguay. The budget impact of switching from TIV to QIV in the Immunization Program was also evaluated. The adapted model includes two modules. The first compared retrospectively Health and Economic outcomes resulting from the use of QIV instead of TIV. The second forecast the spending and savings that would be associated with the switch from TIV to QIV. Our findings estimate that the switch from TIV to QIV during the seasons 2012 to 2017 could have prevented around 2,600 influenza cases, 67 hospitalizations and 10 deaths. An alternative scenario using standardized estimates of the burden of influenza showed that 234 influenza-related hospitalizations and 29 deaths could have been prevented. The estimated annual budget impact of a full switch from TIV to QIV was around USD1,6 million both from the payer and societal perspectives. Those results are mainly driven by vaccine prices and coverage rate. In sum, this manuscript describes how the use of QIV instead of TIV could have prevented influenza cases and subsequent complications that led to hospitalizations and deaths. This could have generated savings for the health system and society, offsetting part of the additional investment needed to switch from TIV to QIV.